Diversity of extracellular matrix morphology in vertebrate skeletal muscle - Sleboda, David A. (J Morphol, 2019)
Existing data suggest the extracellular matrix (ECM) of vertebrate skeletal muscle consists of several morphologically distinct layers: an endomysium, perimysium, and epimysium surrounding muscle fibers, fascicles, and whole muscles, respectively. These ECM layers are hypothesized to serve important functional roles within muscle, influencing passive mechanics, providing avenues for force transmission, and influencing dynamic shape changes during contraction. The morphology of the skeletal muscle ECM is well described in mammals and birds; however, ECM morphology in other vertebrate groups including amphibians, fish, and reptiles remains largely unexamined. It remains unclear whether a multilayered ECM is a common feature of vertebrate skeletal muscle, and whether functional roles attributed to the ECM should be considered in mechanical analyses of non-mammalian and non-avian muscle. To explore the prevalence of a multi-layered ECM, we used a cell maceration and scanning electron microscopy technique to visualize the organization of ECM collagen in muscle from six vertebrates: bullfrogs (Lithobates catesbeianus), turkeys (Meleagris gallopavo), alligators (Alligator mississippiensis), cane toads (Rhinella marina), laboratory mice (Mus musculus), and carp (Cyprinus carpio). All muscles studied contained a collagen-reinforced ECM with multiple morphologically distinct layers. An endomysium surrounding muscle fibers was apparent in all samples. A perimysium surrounding groups of muscle fibers was apparent in all but carp epaxial muscle; a muscle anatomically, functionally, and phylogenetically distinct from the others studied. An epimysium was apparent in all samples taken at the muscle periphery. These findings show that a multi-layered ECM is a common feature of vertebrate muscle and suggest that a functionally relevant ECM should be considered in mechanical models of vertebrate muscle generally. It remains unclear whether cross-species variations in ECM architecture are the result of phylogenetic, anatomical, or functional differences, but understanding the influence of such variation on muscle mechanics may prove a fruitful area for future research.